(untitled) (American Journal of Islam and Society, 1995)
It takes a book like Barbara Freyer Stowasser’s Women in the Qur’an, Traditions and Interpretation to help extricate the complex images of Muslim women from the gross overgeneralization characteristic of popular western media. Truly understanding that complexity requires a look at all of the components that make up the Islamic worldview, from its primary sources ideologically to its cultural history as it has affected the lives of Muslims. Such a look has been offered in Stowasser’s book. I was very excited by the cross-referential methodology proposed by the author in her introduction and her actual use of it throughout the text. She moves among Qur’anic passages, earlier tafasir, hadith traditions, as well as among contenders in modem Islamic discourse: modernists, traditionalists, and fundamentalists (pp. 5-7). As a result, the reader views different responses to ideas about specific women from the Qur’anic text while knowing precisely the source of certain ideas. This is not the usual diatribe that confuses indiscriminately fact with mythology, intellectual tradition with popular culture, and results in misinforming the already ill-informed reader. Moreover, Stowasser avoids the other popular extreme: diminishing everything to a single factor, such as gross misogyny, for example. Although she distinguishes between the various strains that make up a complex picture, she does not merely regurgitate the historical legacy but rather offers critical analysis and demonstrates her capability in deciphering the various components in the internal Islamic debates as well. Perhaps the complexity of the cross-referential methodology limits the breadth of the subject matter. We can understand how complex notions of the place of Muslim women in society have resulted from these various references, even though we get no hint at what that place is from this work. The characters analyzed are limited to the specific female characters given individual attention in the Qur’anic text and to the wives of the Prophet. These models of virtue and .struggle, failure and frustration, can and have ...